Do socio-demographic and anthropometric characteristics predict food choice motives in an Irish working population?. Issue 1 (10th July 2019) - Schliemann, Désirée; Woodside, Jayne V.; Geaney, Fiona; Cardwell, Chris; McKinley, Michelle C.; Perry, Ivan
Abstract: Dietary behaviour is influenced by a complex web of biological, psychological, physiological, social, economic and cultural factors. Understanding socio-demographic and anthropometric characteristics that influence food choice may be important in guiding dietary interventions. The present study aimed to identify whether socio-demographic and anthropometric characteristics influence food choice in an Irish working population. A cross-sectional survey was conducted in 2014 as part of the Food Choice at Work Study, a large clustered non-randomised, controlled trial based in county Cork, Ireland. Information regarding food motives was collected at the 3–4 months follow-up. The 'Food Choice Questionnaire' was used to measure food motives. Multiple linear regression was conducted to test the association between socio-demographic and anthropometric characteristics (age, sex, BMI, education, type of accommodation, living situation, marital status, parental status) and worksite and food motives. A total of 678 employees were included in the analysis. Overall, only a small percentage of food choice was influenced by the characteristics included in this analysis (1·6 to 8·8 %). Sensory appeal and satisfaction were scored most important by all sub-populations. Sex was most often associated with differences in food motives (i.e. all food motives except for familiarity and ethical concern were significantly more important to females compared with males; P = 0·001/ P < 0·001). Worksite, age, BMI and marital status also seemed to play a small role in influencing food choice. The results show that food choice is complex and not easily explained by differences in socio-demographic or anthropometric population characteristics.